Outcome Harvesting: Assessment of the transformations generated by Local Technical Agroclimatic Committees In Latin America - Ramírez Villegas, Julián Armando; Giraldo Mendez, Diana Carolina; Camacho, Kemly; Navarro Racines, Carlos Eduardo; Martínez Barón, Deissy; Prager, Steven D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
During 2019, an analysis process was carried out on the transformations generated by Local Technical Agroclimatic Committees (Mesas Técnicas Agroclimáticas-MTA in Spanish) in the territories where they have been established in the last six years. The study focuses on observable changes in communities, organizations, or institutions that have modified their actions, relationships, policies, and practices in four Latin American countries. Five transformation areas have been identified: i) greater confidence in the quality of climate and agroclimatic information at the local level; ii) enhanced knowledge, understanding, and connection of agroclimatic information; iii) democratization of climate knowledge; iv) transformations in agricultural practices, and v) political advocacy and institutional transformation. Over 140 outcomes or changes were verified in those areas. It has become evident that the MTAs analyzed have encouraged a closer approach of national meteorological institutions to the needs of territories, which in turn has promoted the creation of local practice communities on the application of climate knowledge in decision-making. Indeed, there is evidence that farmers adapt their production practices making decisions based on information on local climate variability, reducing losses and increasing profitability. It has also been shown that that the development of inter-institutional alliances derived from MTAs in the countries helps to build and strengthen local and national public policies for adaptation to climate change and variability in agriculture. Finally, several opportunities and challenges related to leadership and the sustainability of the MTAs establishment process in Latin America were identified.